2016
DOI: 10.1073/pnas.1613417113
|View full text |Cite
|
Sign up to set email alerts
|

Repression of p63 and induction of EMT by mutant Ras in mammary epithelial cells

Abstract: The p53-related transcription factor p63 is required for maintenance of epithelial cell differentiation. We found that activated forms of the Harvey Rat Sarcoma Virus GTPase (H-RAS) and phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) oncogenes strongly repress expression of ΔNp63α, the predominant p63 isoform in basal mammary epithelial cells. This regulation occurs at the transcriptional level, and a short region of the ΔNp63 promoter is sufficient for repression induced by H-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 103 publications
3
50
0
Order By: Relevance
“…We checked the expression profiles of Ras genes (H‐Ras, K‐Ras, N‐Ras) in Tn‐positive vs Tn‐negative CRC cells, and found an increased expression of H‐Ras in cancer cells expressing Tn antigen, whereas the changes of K‐Ras or N‐Ras were not different. Several studies revealed that ectopic expression of oncogenic H‐Ras led to an EMT and increased invasive ability, which were indeed consistent with our observations . We found that knockdown of H‐Ras resulted in a suppression of EMT and reduced the ability of cell migration and invasion, suggesting that H‐Ras could be a key factor responsible for Tn antigen‐induced cancer metastasis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We checked the expression profiles of Ras genes (H‐Ras, K‐Ras, N‐Ras) in Tn‐positive vs Tn‐negative CRC cells, and found an increased expression of H‐Ras in cancer cells expressing Tn antigen, whereas the changes of K‐Ras or N‐Ras were not different. Several studies revealed that ectopic expression of oncogenic H‐Ras led to an EMT and increased invasive ability, which were indeed consistent with our observations . We found that knockdown of H‐Ras resulted in a suppression of EMT and reduced the ability of cell migration and invasion, suggesting that H‐Ras could be a key factor responsible for Tn antigen‐induced cancer metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…We further investigated the mechanisms by which Tn antigen activates EMT. Accumulating evidence shows that Ras signalling activates EMT during cancer metastasis . We reasoned whether Tn antigen has an influence on Ras family proteins (H‐Ras, K‐Ras and N‐Ras), and consequently, activates EMT.…”
Section: Resultsmentioning
confidence: 99%
“…Claudins are suggested to be integral membrane proteins, responsible for maintaining epithelial cell polarity. Repression of p63, a transcription factor required for maintenance of epithelial cell differentiation, induces EMT …”
Section: Discussionmentioning
confidence: 99%
“…One of the techniques used to conduct the prognosis is using a marker to detect immunohistochemically [2]. Marker not only has certain characteristic properties but also has predictive character toward the sensitivity and specificity of breast tumors with specific types [20,21]. TP63, on the other hand, is a nuclear marker of myoepithelial cells frequently expressed on basal epithelial cells of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The basal-like and TNBC were associated [19]. In addition, the expression of p63 protein derived from basal epithelial cells is strongly influenced by the intensity of tumor cell development such as cell nutrition factor [20], chemotherapy, regulation, and p63 protein synthesis [21] both in nucleus and cytoplasm [22].…”
Section: Distribution Of Samplesmentioning
confidence: 99%